2016
DOI: 10.1007/s00415-016-8030-6
|View full text |Cite
|
Sign up to set email alerts
|

Taste dysfunction in multiple sclerosis

Abstract: Empirical studies of taste function in multiple sclerosis (MS) are rare. Moreover, a detailed assessment of whether quantitative measures of taste function correlate with the punctate and patchy myelin-related lesions found throughout the CNS of MS patients has not been made. We administered a 96-trial test of sweet (sucrose), sour (citric acid), bitter (caffeine) and salty (NaCl) taste perception to the left and right anterior (CN VII) and posterior (CN IX) tongue regions of 73 MS patients and 73 matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Clinical evaluation of taste alterations can be done using electrogustometry, chemogustometry and self-administered questionnaires 87 . Electrogustometry may be very useful for diagnosis and monitoring of MS; Sarmiento et al showed that patients with MS presented increased threshold and difficulties to identify tastants for all four classic taste qualities on both anterior (VII) and posterior regions of the tongue (IX) 88 and that such difficulties increased with the progression of MS.…”
Section: Taste Alterationsmentioning
confidence: 99%
“…Clinical evaluation of taste alterations can be done using electrogustometry, chemogustometry and self-administered questionnaires 87 . Electrogustometry may be very useful for diagnosis and monitoring of MS; Sarmiento et al showed that patients with MS presented increased threshold and difficulties to identify tastants for all four classic taste qualities on both anterior (VII) and posterior regions of the tongue (IX) 88 and that such difficulties increased with the progression of MS.…”
Section: Taste Alterationsmentioning
confidence: 99%
“…Patients with multiple sclerosis (MS) present alterations related to the sensing of physiological bodily signals (Rocca et al, 2015), including subclinical deficits in olfaction (Silva et al, 2012) and taste (Doty et al, 2016), and clinical symptoms such as abnormal temperature processing (Davis, Wilson, White, & Frohman, 2010), chronic pain (Michalski, Liebig, Thomae, Hinz, & Bergh, 2011), and fatigue (Krupp, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The olfactory tests were the first, and the MRI imaging scans the last, of the procedures administered on a test day. Findings from non-olfactory components of this program have been published, or are being published, elsewhere (e.g., [5, 35]). In rare cases, the test sessions were distributed across two days, depending upon a subject’s availability, health, and tolerance for the testing procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Correlations between the test scores and disease duration were assessed after parceling out the effects of age. Similarly, correlations were computed between olfactory test scores and the number and volumes of lesions within brain structures with adequate numbers of lesions, as described in detail elsewhere [5, 35]. In the case of lesion volumes, corrections for whole brain volumes were made.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation